Proximate composition of baked foods produced from various composite flour: a review - Guyih, Mulak Desmond; Bongjo, Ndi Betrand; Chi, Eugenie Lum; Muyong, Muyong Gordon; Atam, Fombang Modecai (Journal of Postharvest Technology, 2021)
The use of composite flour in bakery products have increased throughout the years, which aimed at reducing too much reliance on wheat  flour, increasing the nutritional content of foods (micro and macro nutrients) and also preventing post-harvest loses. The proximate  compositions of most bakery products have been studied in developed and developing countries, due to increase consumer knowledge on the  nutritional composition of foods they eat. In this review, the proximate compositions of some popular baked foods (cookies / biscuits, bread  and cakes) were reviewed, pointing out these proximate compositions: moisture, protein, fats, crude fiber, ash and carbohydrates. Their  importance and methods of analysis were also highlighted with reference to several works. The proximate composition was found beneficial,  enhancing the varieties of food products by the use of different composite flour and good in fighting macro and micro nutrient malnutrition.
Keywords: Baking; food; processing; nutrition; postharvest